A semi-analytical model for predicting stress evolution in multilayer coating systems during thermal cycling - Li, Biao (2019)
A semi-analytical model is developed to predict the stress evolution within a multilayer coating system during cyclic thermal loading. This model takes into account the temperature gradient across the thickness of the system, which is the common thermal conditions of the high-temperature protective coatings. The creep deformation and the oxide scale growth processes at the elevated temperature are considered in the theoretical framework. The cases of thermal barrier coatings are analyzed, and finite element analysis is performed for comparisons. The results show that the stress and creep strain fields solved by the semi-analytical method are consistent with the finite element predictions, which confirms the validity of the proposed model. The effects of creep in the system on the stresses and curvature evolutions are discussed. It is found that the large creep rates in the coatings or substrate could facilitate the stress relaxation processes in both of them, whereas the stress evolutions in the oxide scale are virtually unaffected. The curvature of the system may reverse from the concave to convex shape during the thermal cycling when the fast creep relaxations occur in the coatings. Furthermore, the creep deformations in the oxide scale provide benefits in relaxing the huge growth stresses so that the better durability of the system could be obtained